Bioceramic enhances the degradation and bioactivity of iron bone implant. (27th September 2019) - Shuai, Cijun; Li, Yulong; Yang, Youwen; Peng, Shuping; Yang, Wenjing; Qi, Fangwei; Xiong, Shixian; Liang, Huixin; Shen, Lida
Abstract: Iron (Fe) alloy has been recognized as potential bone repair material, due to its favorable mechanical strength and good biocompatibility. However, its too slow degradation rate and poor bioactivity limit the further application. In this study, bredigite, as one kind of bioceramic, was incorporated into Fe implant fabricated by laser additive manufacturing. The incorporated bredigite resulted in a rapid development of corrosion pits due to its fast dissolution, which enlarged the contacting area of Fe matrix to solution. Consequently, the degradation rate of Fe matrix increased from 0.09 to 0.21 mm/year, which could match the healing cycle for bone repair. More significantly, the released nutrient elements (Ca, Mg and Si) from bredigite accelerated the surface mineralization, which promoted cell growth, adhesion and differentiation. In addition, laser additive manufactured Fe/bredigite exhibited favorable mechanical properties, with a yielding strength of 200.4 ± 11.1 MPa and ultimate strength of 315.5 ± 14.8 MPa. Considering all these positive results, Fe/bredigite was a promising material for bone repair application.